PENGARUH KOMPETENSI WIRAUSAHA TERHADAP KEBERHASILAN USAHA PADA RM. PADANG ANGKASA, PADALARANG (The Influence Of Entrepreuneurship Competence To Business Success At RM. PADANG ANGKASA, PADALARANG ) - Aldina Shiratina; Fahd Yudhanegoro (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
Entrepreneurial ability in managing the business very well and encouraged by good science will also serve as sources of labor become a vital object in the implementation of the company. Entrepreneurship as the driving wheel of the company plays an important role in supporting the achievement of business objectives. Entrepreneurial Education and Science is a unity that can not be separated. The purpose of this study is to determine the existing entrepreneurial competence in RM. PADANG ANGKASA, PADALARANG, to know the success of the RM. PADANG ANGKASA, PADALARANG, and to test the effect of competence on the success of entrepreneurial businesses in the RM. PADANG ANGKASA, PADALARANG.  The method used in this research is to census descriptive and verification approaches. This study uses explanatory survey research data collection techniques. This was a census study, by taking the entire population as the sample population totaling 48 employees. Techniques of data collection using interviews, observation, questionnaires and documentation. Analysis method using Pearson product moment correlation and coefficient of determination, as well as t test using SPSS 17.0 for windows. The results showed that entrepreneurial competencies in supporting the success of Business In the calculation of correlation is obtained for (r) = 0.657, the determination coefficient (Kd) = 43.17%, which means Entrepreneurial Competence affect business success is positive and strong. Where as in the calculation of the hypothesis with used t get t value = 5.91, while t table value = 2.013 where t count > t table which means that Ho is rejected, H1 is accepted, based on research by using the t test the two parties with a significant level of 5%, this means that the effect on the Entrepreneurial Competencies of Business Success in RM. PADANG ANGKASA, PADALARANG.  Keywords :    Entrepreneurship Competence and Business Success.